The Review of the Maslahah Mursalah Related to Early Marriage: Implementation and Orientation - Suleman, Frangky; Arifuddin, Qadriani; Saifudin, Saifudin; Khasanah, Fitrohtul; Karimullah, Suud Sarim (Jurnal Dinamika Hukum, 2023)
Child marriage is a controversial issue in many countries, including Indonesia, due to its negative impact on girls. Indonesian law regulates the minimum age for marriage, but there are still gaps in its implementation. This issue also relates to social, economic, and health impacts, such as reproductive health risks and limited access to education. This research aims to review the implementation of child marriage policies, policy orientations, and their impact on the understanding and implementation of maslahah mursalah values. This study uses normative legal research methods to examine the issue of child marriage based on the normative aspects present in applicable legislation. The results of the research indicate that the implementation of child marriage policies based on maslahah mursalah in Indonesia should be holistic, considering social, cultural, religious, and legal aspects. This policy should prioritize the common welfare and protection of children's rights, with an emphasis on education, legal protection, reproductive health, and reducing social stigma. The importance of collaboration between the government, NGOs, religious leaders, and the community in designing and implementing this policy is emphasized. Regular evaluations need to be conducted to ensure the effectiveness of the policy in achieving the goals of child protection and public welfare. Additionally, consideration should be given to the cultural and religious diversity in Indonesia while adhering to international commitments supporting the prohibition of child marriage.